A juxtamembrane basolateral targeting motif regulates signaling through a TGF-β pathway receptor in Drosophila. - Aidan J Peterson; Stephen J Murphy; Melinda G Mundt; MaryJane Shimell; Edward B Leof; Michael B O'Connor (PLoS Biology)
In polarized epithelial cells, receptor-ligand interactions can be restricted by different spatial distributions of the 2 interacting components, giving rise to an underappreciated layer of regulatory complexity. We explored whether such regulation occurs in the Drosophila wing disc, an epithelial tissue featuring the TGF-β family member Decapentaplegic (Dpp) as a morphogen controlling growth and patterning. Dpp protein has been observed in an extracellular gradient within the columnar cell layer of the disc, but also uniformly in the disc lumen, leading to the question of how graded signaling is achieved in the face of 2 distinctly localized ligand pools. We find the Dpp Type II receptor Punt, but not the Type I receptor Tkv, is enriched at the basolateral membrane and depleted at the junctions and apical surface. Wit, a second Type II receptor, shows a markedly different behavior, with the protein detected on all membrane regions but enriched at the apical side. Mutational studies identified a short juxtamembrane sequence required for basolateral restriction of Punt in both wing discs and mammalian Madin-Darby canine kidney (MDCK) cells. This basolateral targeting (BLT) determinant can dominantly confer basolateral localization on an otherwise apical receptor. Rescue of punt mutants with transgenes altered in the targeting motif showed that flies expressing apicalized Punt due to the lack of a functional BLT displayed developmental defects, female sterility, and significant lethality. We also show that apicalized Punt does not produce an ectopic signal, indicating that the apical pool of Dpp is not a significant signaling source even when presented with Punt. Instead, we find that basolateral presentation of Punt is required for optimal signaling. Finally, we present evidence that the BLT acts through polarized sorting machinery that differs between types of epithelia. This suggests a code whereby each epithelial cell type may differentially traffic common receptors to enable distinctive responses to spatially localized pools of extracellular ligands.